Academic Management Supervision of the Principal Madrasah - Riyono; Normuslim; Muslimah (International Journal of Community Engagement Payungi, 2021)
The aim of this article was to describe how the principles, objectives, the function and approach of supervision, as well as how the head of madrasah carries out the planning, implementation and follow-up of academic supervision at madrasah. The researchers used literature review. The step was to trace the printed and electronic references regarding the supervision of madrasah principals in general, then narrow it down to the sub-focus of the discussion, namely the academic supervision of madrasah principals. Once deemed sufficient, the authors describe it systematically. The findings of this study showed that academic supervision was an effort to help teachers develop their abilities in achieving learning goals. The essence of academic supervision was not any assessing the performance of teachers in managing the learning process, but helping teachers  to develop their professional abilities. Academic supervision that must be carried out by the principal of madrasah includes: planning an academic supervision program, carrying out academic supervision, following up on the results of academic supervision aimed at increasing the professionalism of teachers as professional educators.